Evaluation of Customer Service in Integrated Supply Chains of Manufacturing and Trading Companies - Joanna DYCZKOWSKA; Jarosław POZNAŃSKI (Communications of International Proceedings, 2021)
Logistics process management may be comprehensive and it might cover all logistics processes and activities. The aim of the publication is to analyse customer service in an integrated supply chain of manufacturing and trading companies, where the integrator is a logistics operator. The main hypothesis: The role of the main service provider as an integrator in the supply chain affects the realization of objectives. The research methods: used include a literature analysis, a comparative analysis and a diagnostic survey method using questionnaire technique. The analysis and configuration of the results allow the an evaluation of logistic customer service in the three links, which leads to a differentiation of the logistics customer service by the logistics operator in supply chains. Specific mechanisms preceding and linking LCS that influence customer satisfaction are presented.
Keywords: Customer service; SCM